Effects of a polysaccharide-based multi-ingredient supplement on salivary immunity in non-elite marathon runners - Roca, Emma (J Int Soc Sports Nutr, 2019)
BACKGROUND: Extreme exercise may alter the innate immune system. Glycans are involved in several biological processes including immune system regulation. However, limited data regarding the impact of glycan supplementation on immunological parameters after strenuous exercise are available. We aimed to determine the impact of a standardized polysaccharide-based multi-ingredient supplement, Advanced Ambrotose© complex powder (AA) on salivary secretory Immunoglobulin A (sIgA) and pro- and anti-inflammatory protein levels before and after a marathon in non-elite runners. METHODS: Forty-one male marathon runners who completed the 42.195 km of the 2016 Barcelona marathon were randomly assigned to two study groups. Of them, n = 20 (48%) received the AA supplement for 15 days prior the race (AA group) and n = 21 (52%) did not receive any AA supplement (non-AA group). Saliva and blood samples were collected the day before the marathon and two days after the end of the race. Salivary IgA, pro-inflammatory chemokines (Gro-alpha, Gro-beta, MCP-1) and anti-inflammatory proteins (Angiogenin, ACRP, Siglec 5) were determined using commercially ELISA kits in saliva supernatant. Biochemical parameters, including C-reactive protein, cardiac biomarkers, and blood hemogram were also evaluated. RESULTS: Marathon runners who did not receive the AA supplement experienced a decrease of salivary sIgA and pro-inflammatory chemokines (Gro-alpha and Gro-beta) after the race, while runners with AA supplementation showed lower levels of anti-inflammatory chemokines (Angiogenin). Gro-alpha and Gro-beta salivary levels were lower before the race in the AA group and correlated with blood leukocytes and platelets. CONCLUSIONS: Changes in salivary sIgA and inflammatory chemokines, especially Gro-alfa and Gro-beta, were observed in marathon runners supplemented with AA prior to the race. These findings suggested that AA may have a positive effect on immune response after a strenuous exercise.